The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.5304/jafscd.2010.012.002
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the local food supply capacity of Detroit, Michigan

Abstract: Urban agriculture is touted as a strategy for more locally reliant food systems, yet there is little understanding of its potential food provisioning capacity. Using Detroit, Michigan as an example, we use secondary data to develop a methodology for estimating the acreage required to supply, as far as seasonally possible, the quantity of fresh fruits and vegetables consumed by city residents. We compare these requirements with a catalog of the publicly owned, vacant parcels in Detroit to assess the feasibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 22 publications
(19 reference statements)
1
60
0
2
Order By: Relevance
“…Cool, wet winters and warm, dry summers allow for over 170 different crops to be grown in this fertile region (ODA, 2009b). Steady rainfall occurs from December through February, followed by relatively aridity in summers, which average only five percent of the total annual average precipitation (PNW-ERC, 2002 (Coba, 2010). Despite these numbers representing Oregon as a whole (rather than the Willamette Valley growing region alone) and the …”
Section: From Grass Seed To Grainsmentioning
confidence: 99%
“…Cool, wet winters and warm, dry summers allow for over 170 different crops to be grown in this fertile region (ODA, 2009b). Steady rainfall occurs from December through February, followed by relatively aridity in summers, which average only five percent of the total annual average precipitation (PNW-ERC, 2002 (Coba, 2010). Despite these numbers representing Oregon as a whole (rather than the Willamette Valley growing region alone) and the …”
Section: From Grass Seed To Grainsmentioning
confidence: 99%
“…Applying a distribution lens to the existing literature yields similar results to the food access analysis in that several articles theorize idealized distribution systems, showing the capacity of hypothetical urban and peri-urban farms to supply distribution networks that meet most urban food demands [40,[53][54][55][56][57]. Others highlight barriers and challenges farmers face in practice around distributing their produce to those in need while maintaining their operations [72,73].…”
Section: Food Distribution: How Do Urban Farmers Get Their Produce Tomentioning
confidence: 61%
“…Other theoretical mapping analyses have also found that urban and peri-urban farms can supply significant amounts of food demand in urban centers: from 5-10% of city vegetable demand supplied by expanded UA on public lands in Oakland [18] to 30% of seasonal vegetable demand in Detroit [57], to 100% of nutritional needs in Southeastern Minnesota [54]. However, very few studies directly quantify how much urban produced food is actually being consumed by low-income food insecure communities, requiring observational and qualitative research methods.…”
Section: Spatial Analyses Highlight Productive Potential and Uneven Dmentioning
confidence: 99%
“…Vacant Lot Cultivation Associations facilitate gardening on vacant land and encourage the poor to grow food for sale and self-consumption [26] and land trust lease and acquisition programs enable communities to maintain gardens [11]. In underserved neighborhoods, Cooperative Extension support for food production [26] operate side-lot or "abutter" programs that encourage residents to manage the land between buildings, as well as a more recent integration of community garden and urban agriculture programs that is contributing to the creation of more sustainable planning processes [27][28][29].…”
Section: Greening Vacant Lotsmentioning
confidence: 99%